2009
DOI: 10.2225/vol12-issue4-fulltext-6
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of lead(II) and chromium(VI) on groundnut hull: Equilibrium, kinetics and thermodynamics study

Abstract: Abbreviations: FTIR: Fourier transform infrared rpm: rotations per minute SEM: scanning electron microscopeThe biosorption of lead(II) and chromium(VI) on groundnut hull was investigated. Batch biosorption experiments were conducted to find the equilibrium time and biosorption capacity. Effect of parameters like pH, temperature and initial metal concentration was studied. The maximum biosorption capacity of lead(II) and chromium(VI) was found to be 31.54 ± 0.63 and 30.21 ± 0.74 mg g -1 , respectively. The opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 31 publications
(44 reference statements)
1
52
0
3
Order By: Relevance
“…The D-R isotherm assumes biosorption on a heterogeneous surface 20,21 . The D-R isotherm is given by: ln qe= ln qo-Kdε 2 (6) Kd is identified from mean free energy E, qo is the infusion capacity and ε is the Polanyi potential.…”
Section: D-r Isothermmentioning
confidence: 99%
“…The D-R isotherm assumes biosorption on a heterogeneous surface 20,21 . The D-R isotherm is given by: ln qe= ln qo-Kdε 2 (6) Kd is identified from mean free energy E, qo is the infusion capacity and ε is the Polanyi potential.…”
Section: D-r Isothermmentioning
confidence: 99%
“…For example, researchers have documented that exposure to Cr(VI) can cause long-term and serious public health hazards such as skin irritation, lung cancer, as well as kidney, liver and gastric damage (Qaiser et al 2009;Vinodhini and Das 2009). Cr(VI) also poses significant ecological risk.…”
Section: Introductionmentioning
confidence: 99%
“…The dried biomass was then preserved in air-tight polyethene paper to protect it from moisture and make ready for analysis. 13 The adsorbent was used in their natural form without any form of modification.…”
Section: Preparation Of Adsorbentmentioning
confidence: 99%
“…The adsorption capacity q L (mg/g) for cadmium (6.993mg/g) was lower than that of lead (58.82mg/g), suggesting that the amount of Pb(II) sorbed per unit mass of the adsorbent was higher than that of Cd(II). Qaiser et al 13 reported the maximum sorption capacities for lead on groundnut hull (31.54mg/g) and baggase fly ash (2.5mg/g). Table 3 show the comparison of Sorghum husk with other agricultural and commercial adsorbents using their maximum adsorption capacity (q max -mg/g) for the adsorption of Cd(II) and Pb(II).…”
mentioning
confidence: 99%